2011
DOI: 10.1371/journal.pone.0025407
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality Directs Contrasting Food Collection Behavior and Nutrient Regulation Strategies in Ants

Abstract: Long-lived animals, including social insects, often display seasonal shifts in foraging behavior. Foraging is ultimately a nutrient consumption exercise, but the effect of seasonality per se on changes in foraging behavior, particularly as it relates to nutrient regulation, is poorly understood. Here, we show that field-collected fire ant colonies, returned to the laboratory and maintained under identical photoperiod, temperature, and humidity regimes, and presented with experimental foods that had different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 42 publications
2
43
1
Order By: Relevance
“…Do species with a broader fundamental nutritional niche occur over wider geographic ranges or different habitat types? Studies using the geometric approach in the laboratory should in the future include more complex paradigms as nutrient regulation strategies may change with colony size or seasonality [38].…”
Section: Interspecific Differences In Nutritional Needsmentioning
confidence: 99%
“…Do species with a broader fundamental nutritional niche occur over wider geographic ranges or different habitat types? Studies using the geometric approach in the laboratory should in the future include more complex paradigms as nutrient regulation strategies may change with colony size or seasonality [38].…”
Section: Interspecific Differences In Nutritional Needsmentioning
confidence: 99%
“…Foragers in experimentally manipulated colonies might revert to inner-nest tasks -a behavioural shift sometimes associated with an increase in lipid reserves Nakata, 1995;Amdam et al, 2005;Baker et al, 2012;Kuszewska and Woyciechowski, 2013;Bernadou et al, 2015). Lastly, social insects function as long-lived 'super-organisms' that are often confronted with food shortage or food imbalance due to annual seasonal fluctuations in food availability (Cook et al, 2011). This feature of the natural history of social insects offers the intriguing possibility of disentangling the effect of age, task and fat reserves on resistance to nutritional stresses.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that predators were more abundant in the rainy months, herbivores were restricted to this same period and omnivores were more abundant during the dry season. Changes in the pattern of ant's composition at different times occur due to variations in eating habitats and in the specie's ability to use distinct resources (Meyer et al, 2010;Cook et al, 2011;Castaño-Meneses, 2014).…”
Section: Discussionmentioning
confidence: 99%